2016
DOI: 10.1088/0957-0233/27/9/095901
|View full text |Cite
|
Sign up to set email alerts
|

3D-calibration of three- and four-sensor hot-film probes based on collocated sonic using neural networks

Abstract: High resolution measurements of turbulence in the atmospheric boundary layer (ABL) are critical to the understanding of physical processes and parameterization of important quantities, such as the turbulent kinetic energy dissipation. Low spatio-temporal resolution of standard atmospheric instruments, sonic anemometers and LIDARs, limits their suitability for fine-scale measurements of ABL. The use of miniature hot-films is an alternative technique, although such probes require frequent calibration, which is l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…The transfer function can either be computed for each x-probe separately while averaging the redundant 𝑱 component or to be constructed using 4 voltage inputs with 3 velocity outputs. Kit and Liberzon (2016) (Kit and Liberzon 2016) already demonstrated that neither is superior to the other and we confirm this result. Finally, as the hotfilms gradually degrade with use resulting in measurement drift, the traditional jet-based calibration was performed twice.…”
Section: Different Calibration Approachessupporting
confidence: 88%
See 4 more Smart Citations
“…The transfer function can either be computed for each x-probe separately while averaging the redundant 𝑱 component or to be constructed using 4 voltage inputs with 3 velocity outputs. Kit and Liberzon (2016) (Kit and Liberzon 2016) already demonstrated that neither is superior to the other and we confirm this result. Finally, as the hotfilms gradually degrade with use resulting in measurement drift, the traditional jet-based calibration was performed twice.…”
Section: Different Calibration Approachessupporting
confidence: 88%
“…NN have also successfully been used for complex function approximations. Several studies have shown that regression NN are capable of capturing the velocity-voltage relationship estimates strikingly well in hotwire anemometry (Kit and Grits 2011;Fernando et al 2015;Kit and Liberzon 2016;Kit et al 2017;Goldshmid and Liberzon 2018). In these studies, the training set (TS) used for each model was based on delicately selected minutes that contained mean velocities that covered the entire range of interest and high rms values of velocity fluctuations.…”
Section: Different Calibration Approachesmentioning
confidence: 99%
See 3 more Smart Citations